Climate resilience and water security – key messages from the REACH Kenya programme 2015-2024 - Olago, D; Mumma, A; Ouma, G; Opondo, M; Bukachi, S; Omia, D; Tanui, F; Odira, M; Ong’ech, D; Wanguba, B (University of Oxford, 2024)
The links between water security and climate are broadly well understood but poorly evidenced, particularly at the scales appropriate for policy and practice to advance water security in low and middle-income countries. This report from the Institute for Climate Change and Adaptation (ICCA) at the University of Nairobi, Kenya provides a summary of key messages from research conducted under the REACH Kenya programme (2015-2024).